Effectiveness of the interventions in preventing the progression of pre-frailty and frailty in older adults: a systematic review protocol - Apóstolo, J.
The objective of this review is to identify the effectiveness of the interventions in preventing progression of pre-frailty and frailty in older adults. More specifically, the review questions are: - What is the effectiveness of interventions in preventing or reducing frailty in older adults? - How does effectiveness vary with degree of frailty? - Are there factors that influence the effectiveness of interventions? - What is the economic feasibility of interventions for pre-frailty and frailty?